How smallholder farmers adapt to climate change: Stories from India - Kumari I (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2011)
Indramani Kumari is a female farmer from the village Jamnapur in India, who talks about the lack of water and how it made the villagers lives fragile. As a consequence the youths are leaving the village, the fields are producing less, and the boreholes and rivers are drying out. More people have to go hungry these days she explains.